2015 International Conference on Industrial Engineering and Operations Management (IEOM) 2015
DOI: 10.1109/ieom.2015.7093810
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Big Data Analytics to Nigerian mobile phone industry

Abstract: In the last half decade or so, the buzz phrase in the business and research arena is Big Data and Big Data Analytics. One industry that can reap substantial benefits from big data and analytics is the mobile phone industry. Nigeria in the West Africa is one country where mobile phone market is considerably big. Over 90 per cent of individuals and corporate businesses completely rely on the mobile industry for their day-to-day transactions. Embracing advanced analytics of big data by the mobile operators in Nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A study conducted on Nigeria's general election of 2015 [16] revealed social media as the major influencer and that SMA can contribute in predicting trends that may influence developing economies. On the other hand, the substantial benefits from Big Data and analytics that were reaped by the mobile phone industry in Nigeria [58] revealed that proper correlations of social media data can help to reveal more complete and deeper insight of customer needs, thus enriching the operators with more revenue.…”
Section: Discussion and Implications For Research In Africamentioning
confidence: 99%
“…A study conducted on Nigeria's general election of 2015 [16] revealed social media as the major influencer and that SMA can contribute in predicting trends that may influence developing economies. On the other hand, the substantial benefits from Big Data and analytics that were reaped by the mobile phone industry in Nigeria [58] revealed that proper correlations of social media data can help to reveal more complete and deeper insight of customer needs, thus enriching the operators with more revenue.…”
Section: Discussion and Implications For Research In Africamentioning
confidence: 99%
“…In the telecommunications industry, Big Data Analytics (BDA) revolutionizes operations by empowering operators to harness novel data sources, extracting invaluable insights into customer behavior. Consequently, operators can tailor offerings more precisely, enhancing revenues while curbing expenses [32]. BDA solutions equip telecom operators with the capability to handle diverse data types, whether structured or unstructured, regardless of the rate of data generation.…”
Section: Big Data Analytics In Telecommunication Servicesmentioning
confidence: 99%
“…Scalability and extensibility are the parameters used for the evaluation of BDI technologies. Nwanga et al studied the impact of big data analytics in mobile phone industry [40]. This study has revealed that BDI solutions and big data analytics has an impact on the growth of the telecommunication industry by adding huge data insights.…”
Section: Review Of Communication Sectormentioning
confidence: 99%